THE REPRESENTATION OF BRUNEI’S SHARIA LAW IN NEW STRAIT TIMES AND BANGKOK POST - Oktavia, Luluk Kholidatul; Sahiruddin, Sahiruddin; Khasanah, Ismatul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
The purpose of this study is to discover positive-self and negative-other representations of Brunei’s Sharia Law on LGBT through the lexical choices used by the New Strait Times and Bangkok Post also reveals the ideology from both of the media. This study uses a qualitative approach with critical discourse analysis as the research design. Following Van Dijk’s analytical framework, the words were selected and classified into word class, type of meaning (lexical or contextual), and category (positive or negative).  Ideology from both media is obtained from the cognition analysis of the journalist's expression based on the co-text, context, and social context (social condition). The result showed that both media used lexical choices that indicate positive representation of LGBT by stating LGBT as victims, while negative representation on Brunei’s Government, Muslim, and Sharia law as a persecutor. There were four methods in indicating the positive representation of LGBT; noun/noun phrase representation, detailed information on a noun, verb indicating accusation, and verb indicating discrimination; also there were three methods used to indicate negative representation of Brunei’s Government, Muslim, and Sharia law; noun/ noun phrase representation, verb indicating negative actions, and verb indicating provocations.